Clinical Manifestations of IgG4-Related Disease in the Pharynx: Case Series and Review of the Literature. (March 2015) - Reder, Lindsay; Della-Torre, Emanuel; Stone, John H.; Mori, Matthew; Song, Phillip
Objective: The objective of this report is to characterize IgG4-related disease (IgG4-RD) as it is manifested in the head and neck and describe a series of patients with a rarely described presentation in laryngopharyngeal subsites. Methods: Here, we illustrate the presentation and clinical course of 3 patients with laryngopharyngeal manifestations of IgG4-RD, including the manner of diagnosis and effective treatment. Results: Three patients with laryngopharyngeal lesions were ultimately diagnosed with IgG4-RD after lengthy work-up. The diagnostic criteria and treatment protocols are explained. Conclusion: IgG4-related disease is a fibroinflammatory disorder now described in almost every organ system. The head and neck regions are among the most common areas of involvement, however, reports of laryngopharyngeal involvement are rare. We also summarize current knowledge of this entity and discuss established diagnostic criteria and clinical findings.